The Discursive Figuration of U.S. Supremacy in Narratives Sympathetic To Undocumented Immigrants - Lawston, Jodie Michelle (Social justice, 2009)
This article analyzes the immigration debate in the United States by examining its representation in mass media. An episode of the reality television program "30 Days," the documentary film "Under the Same Moon," the nonfiction book "Enrique's Journey," and the short story "Cariboo Café" are examined. The debate is framed as divided between a belief that illegal U.S. immigrants should be prosecuted and deported and a belief that illegal U.S. immigrants should be accepted. Focus is given to U.S. immigrants from Mexico, and it is suggested that the U.S. is depicted as superior to Mexico across the media.